2023
DOI: 10.3389/fendo.2023.1142327
|View full text |Cite
|
Sign up to set email alerts
|

Jinlida granules combined with metformin improved the standard-reaching rate of blood glucose and clinical symptoms of patients with type 2 diabetes: secondary analysis of a randomized controlled trial

Abstract: BackgroundPrevious studies found that Jinlida granules could significantly reduce blood glucose levels and enhance the low-glucose action of metformin. However, the role of Jinlida in the standard-reaching rate of blood glucose and improving clinical symptoms has yet to be studied. We aimed to elaborate on the efficacy of Jinlida in type 2 diabetes (T2D) patients who experience clinical symptoms based on secondary analysis of a randomized controlled trial.MethodsData were analyzed from a 12-week, randomized, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…JLD, a kind of TCM prescription, has been clinically used for the treatment of T2DM in China. Its curative effect as a single or add-on medication has been verified 10 , 11 . However, the bioactive components and the underlying mechanism of JLD against T2DM remain unclear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…JLD, a kind of TCM prescription, has been clinically used for the treatment of T2DM in China. Its curative effect as a single or add-on medication has been verified 10 , 11 . However, the bioactive components and the underlying mechanism of JLD against T2DM remain unclear.…”
Section: Discussionmentioning
confidence: 96%
“…JLD can greatly reduce the level of HbA1c especially in those with HbA1c > 8.5%, significantly alleviate insulin resistance in patients with hyperinsulinemia (insulin levels > 20 mU/L) and improve β-cell function with hypoinsulinemia (insulin levels ≤ 20 mUI/L) 10 . JLD combining with hypoglycemic agent metformin can effectively improve the standard-reaching rate of blood glucose and clinical symptoms such as thirst, fatigue, polyuria, etc 11 . The studies of mechanisms showed JLD can ameliorate insulin resistance by up-regulating the insulin signaling pathway and reducing skeletal muscle lipid content 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%